IMPLIKASI CONSTITUSIONAL COMPLAINT TERHADAP PERLINDUNGAN HAK KONSTITUSIONAL - Pramudya; Dinda Heidiyuan Agustalita; Dwi Wachidiya Ningsih (Judge : Jurnal Hukum, 2026)
The urgency of implementing a constitutional complaint mechanism in Indonesia arises from the restrictive jurisdiction of the Constitutional Court (MK), which is currently limited to abstract judicial review, thereby failing to address casuistic violations of fundamental rights stemming from judicial decisions and executive actions. Using a normative legal research method with statute and case approaches, this study analyzes the juridical position and implications of adopting this mechanism from the perspective of constitutional supremacy. The results indicate that constitutional complaint serves as a transformational instrument that shifts the MK’s role from judex juris to judex facti through concrete review, effectively filling the legal lacuna within Article 24C of the 1945 Constitution. While institutional challenges such as judicial backlog and risks of abuse of process persist, these can be mitigated through the principle of subsidiarity (exhaustion of legal remedies) and procedural restructuring. Ultimately, the adoption of this mechanism strengthens the checks and balances system and solidifies the MK’s position as the "final arbiter" and "center of gravity" for substantive justice, ensuring the protection of non-derogable rights and harmonizing the Indonesian judiciary with modern global constitutionalism standards.